2007
DOI: 10.1016/j.amjsurg.2006.08.069
|View full text |Cite|
|
Sign up to set email alerts
|

Enhancing skin wound healing by direct delivery of intracellular adenosine triphosphate

Abstract: Background-A new intracellular adenosine triphosphate (ATP) delivery technique has been developed and was tested for skin wound care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 29 publications
1
67
0
Order By: Relevance
“…The activation of this enzyme leads to an increase in the production of ATP that is required for numerous cellular functions providing both energy and phosphates required for the regulation of cellular functions. Moreover, addition of external ATP was shown to stimulate wound healing in an animal model [34]. Although no increase in contraction was found in mice treated with external ATP, in vitro observations suggest that ATP increases wound contraction by serving both as an energy source for generation of contractile force and motility, and as a phosphate donor for kinase reactions regulating contraction [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of this enzyme leads to an increase in the production of ATP that is required for numerous cellular functions providing both energy and phosphates required for the regulation of cellular functions. Moreover, addition of external ATP was shown to stimulate wound healing in an animal model [34]. Although no increase in contraction was found in mice treated with external ATP, in vitro observations suggest that ATP increases wound contraction by serving both as an energy source for generation of contractile force and motility, and as a phosphate donor for kinase reactions regulating contraction [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Liposome encapsulated adenosine triphosphate (ATP) (Arakawa et al, 1998) can be used for direct energy delivery and has shown a protective effect in intestinal injury from hemorrhagic shock (Zakaria el et al, 2005) and skin wound healing (Chiang et al, 2007). Because of the enriched purinergic receptors in nerve cells, direct energy delivery has not been successful in the nervous system.…”
Section: Metabolic Suppression and Energy Deliverymentioning
confidence: 99%
“…Improvement of ischemic skin flap survival used in surgery when exposed to ATP has been described (Boss et al, 1984;Cikrit et al, 1984;Zimmerman et al, 1987;Knight et al, 1989), perhaps because of its vasodilator effects (Kuzon et al, 1985). Direct Mg-ATP delivery to cutaneous wounds accelerates healing, perhaps by increasing synthesis of vascular endothelial growth factor (Chiang et al, 2007).…”
Section: G Skin Vesselsmentioning
confidence: 99%